Peluang dan Tantangan Bagi Perusahaan Multinasional di Tengah Agenda MiC 2025 Tiongkok - Hasna Dherin Syakira; Aisyah Zakiyah Nur Aini; Sovira Hikari Luna Shinkoo (Jurnal sosial dan sains, 2023)
Background: Since the economic reforms in 1978, multinational companies have begun to arrive, invest, and operate in China. This was because China had low wages, huge markets, and loose government policies. China is often associated with a negative perception as a center for cheap labor and low-quality products. The MiC 2025 agenda aims to change that negative perception. Besides, this agenda also plans to catch up with China's high-tech in the global market. This paper uses the neo-mercantilism theory, assuming that the Chinese government's initiation to accumulate state wealth by protecting the domestic market and supporting foreign investment. Through MiC 2025, the government plans to strengthen China's dominance in the global market. Purpose: This paper aims to describe the influence of the MiC 2025 agenda on multinational companies (MNCs) in China. Methods: This research uses descriptive qualitative research methods. Results: The results show that MNCs receive both opportunities and challenges from the realization of the MiC 2025 agenda, which the author divides into 4 major subchapters, namely 1) economic competition, 2) collaboration and technology transfer, 3) robotization of labor, and 4) tariff war with the United States. Conclusion: MNCs need to adapt and restructure amidst the MiC 2025 agenda initiated by the government to operate optimally.